Modified mclaughlin technique for neglected locked posterior dislocation of the shoulder: A case report - Ahmad, Sabeel; Dhingra, Mohit; Mishra, Dipun; Jain, Aakriti (Indian Journal of Case Reports, 2020)
Posterior dislocation of the glenohumeral joint is a rare injury accounting 2-4% of all shoulder dislocation and its annual incidence is 0.6% in 100000. This case report is related toneglected posterior shoulder dislocation after an electric shock which was treated by the modified Mc-Laughlin technique after 2 months of injury. Several surgical techniques have been described for the treatment of posterior shoulder dislocation depending on the time elapsed between the injury and diagnosis and the presence of the humeral head impression fracture. Common treatment methods include McLaughlin procedure, filling of defects with allograft or autograft, glenoid augmentation and shoulder prosthesis. Using this technique, the shape of the humeral head was nearly restored with the impaction of autograft from the iliac crest and transfer of lesser tuberosity along with subscapularis into the defect created due to the impaction of the humeral head against glenoid margins.